2020
DOI: 10.1002/rra.3707
|View full text |Cite
|
Sign up to set email alerts
|

New grassland riparian zone delineation method for calculating ecological water demand to guide management goals

Abstract: River flow provides water that maintains the ecological health of both the river itself and the adjoining riparian zones. However, there is a lack of clear definition and identification method of the riparian zone of inland river basins with narrow river channels and anthropogenic intervention reservoirs. In this study, we developed a new method to delineate semiarid grassland riparian zones by taking the Xilin River (Inner Mongolia, China) basin as a case study for providing an opportunity for a more accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As outlined in the methodology, the riparian zones, for the needs of this study, were delineated automatically using GIS. This process was not based on data, which are commonly used for this type of task—for example, hydrogeomorphological delimitation (Betz, Lauermann, & Cyffka, 2018; Holmes & Goebel, 2011), a combination of hydrological information and UAV images (Lan & Rui‐Hong, 2020) or certain automated algorithms (Bhowmik, Metz, & Schäfer, 2015). It was based on a survey of a sample of sites in near‐natural conditions, in which the width of riparian zones was measured.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in the methodology, the riparian zones, for the needs of this study, were delineated automatically using GIS. This process was not based on data, which are commonly used for this type of task—for example, hydrogeomorphological delimitation (Betz, Lauermann, & Cyffka, 2018; Holmes & Goebel, 2011), a combination of hydrological information and UAV images (Lan & Rui‐Hong, 2020) or certain automated algorithms (Bhowmik, Metz, & Schäfer, 2015). It was based on a survey of a sample of sites in near‐natural conditions, in which the width of riparian zones was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Their study reported that raw UAS data "do not" work well for predicting ground-level elevation of tidal marshes, likely because a DSM is not equivalent to a DEM [28]. Other projects in the realm of abiotic mapping involve RGB analysis of soil structure and infiltration [131], delineations of riparian zones [125], and saltmarsh shoreline deposition [126], in addition to thermal analysis of river to floodplain connectivity [127], river temperature heterogeneity in fish habitats [45], and peatland groundwater seepage detection [32].…”
Section: Abiotic Surveysmentioning
confidence: 99%